Concise approach to pyrrolizino[1, 2-b]indoles from indole-derived donor–acceptor cyclopropanes. Issue 66 (28th June 2016) - Villemson, Elena V.; Budynina, Ekaterina M.; Ivanova, Olga A.; Skvortsov, Dmitriy A.; Trushkov, Igor V.; Melnikov, Mikhail Ya.
Abstract : A direct approach to previously unexplored pyrrolizidino[1, 2- b ]indole system from indole-derived donor–acceptor cyclopropanes based on a sequence of three synthetic steps was developed. Abstract : Developed here is a direct three-step approach to a previously unexplored pyrrolizino[1, 2- b ]indole system based on a sequence of three synthetic steps: (a) one-pot azide ion promoted ring opening of the indole-derived donor–acceptor cyclopropane and Krapcho dealkoxycarbonylation; (b) Vilsmeier–Haack formylation; (c) tandem Staudinger/intramolecular aza-Wittig reaction and reductive cyclization realized in a one pot fashion.